Association of Anthropometric and Nutrition Status Indicators with Hand Grip Strength and Gait Speed in Older Adults. Issue 3 (2nd August 2018) - Mendes, Joana; Afonso, Cláudia; Moreira, Pedro; Padrão, Patrícia; Santos, Alejandro; Borges, Nuno; Negrão, Rita; Amaral, Teresa F.
Abstract: Background: How nutrition status indicators relate to function in older adults is an issue that needs to be explored. This study aimed to quantify the associations of anthropometric parameters and nutrition status indicators with hand grip strength (HGS) and gait speed (GS) in older adults. Methods: A cross‐sectional observational study was conducted in a population‐based sample of 1500 older adults ≥65 years old. Logistic regression models were used to explore the associations between anthropometric, nutrition, and functional measures. Results: Lower values of height, mid‐arm muscle circumference, and calf circumference, as well as higher values of waist circumference, were associated with both low GS and HGS. The adjusted odds ratio (OR) for low GS was around 2‐fold higher in participants presenting risk for undernutrition or undernutrition. The adjusted OR (95% confidence interval) for low HGS was 1.54 (1.01–2.36) in women and 1.57 (0.91–2.72) in men at risk for undernutrition/undernutrition. Conclusions: In older adults, lower values of height and calf circumference, as well as higher waist circumference, were associated with both low GS and HGS. Lower values of mid‐arm muscle circumference were also associated with low values of both functional parameters only in men. The risk for undernutrition/undernutrition was more strongly associated with low GS than with low HGS in both women and men.